State-of-the-art review of physical and mechanical properties of natural fibre-reinforced cementitious matrix composite - Ngoc Tu, Do; Manh Tien, Tran; Duc Tho, Pham (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2023)
In Viet Nam, natural fibre-reinforced cementitious matrix (N-FRCM) can be a material solution in some situations and works if research is oriented. This paper presents a state-of-the-art review of the physical and mechanical properties of N-FRCM composite. By inheriting previous review studies in the literature, this paper updates more on the experimental studies on the N-FRCM composite in the last decade. The review addresses, firstly the mechanical properties of constituent materials in N-FRCM as natural fibres, cementitious matrix, and natural fibre/cementitious matrix interface. Secondly, it addresses the physical and mechanical properties of N-FRCM composite, including the density, thermal and sound insulation, and compressive and tensile strengths. The paper then discusses the main factors that influence the properties of N-FRCM materials. Finally, the conclusion of this review terminates this paper.